A Fuzzy Set-Based Approach to Multi-objective Multi-item Solid Transportation Problem Under Uncertainty - Dalman, Hasan; Guzel, Nuran; Sivri, Mustafa (SPRINGER, 2016)
In this paper, a multi-objective multi-item solid transportation problem (MOMISTP) with parameters, e.g., transportation costs, supplies, and demands, as trapezoidal fuzzy variables is formulated. In this MOMISTP, there are limitations on some items and conveyances so that some special items cannot be carried by means of some special conveyances. With the use of the nearest interval approximation of trapezoidal fuzzy numbers, an interval programming model is constructed for the fuzzy MOMISTP and then this model is turned into its deterministic form. Then, a new interval fuzzy programming approach is developed to obtain the optimal solution of the problem. Finally, a numerical example is presented for illustration.
Keywords: Multi-objective multi-item solid transportation problem; Fuzzy decision making; Interval programming; Order relations; INTERVAL-COEFFICIENTS; PROGRAMMING APPROACH; GENETIC ALGORITHM; NUMBERS; OPTIMIZATION; CONSTRAINTS; PARAMETERS; VARIABLES; Automation & Control Systems; Computer Science